Evaluation of the effects of future climate change on grape quality through a physically based model application: a case study for the Aglianico grapevine in Campania region, Italy. (March 2017) - Bonfante, A.; Alfieri, S.M.; Albrizio, R.; Basile, A.; De Mascellis, R.; Gambuti, A.; Giorio, P.; Langella, G.; Manna, P.; Monaco, E.; Moio, L.; Terribile, F.
Abstract: Water deficit limiting yields is one of the negative aspects of climate change. However, this applies particularly when emphasis is on biomass production (e.g. for field crops), but not necessarily for plants where quality, not quantity is most relevant. For grapevine development, mild water stress occurring during specific phenological phases is an important factor when producing good quality wines. It induces the production of anthocyanins and aroma precursors and then could offer an opportunity to increase winegrower's income. A multidisciplinary study was carried out in Campania region (Southern Italy), an area well known for high quality wine production. Growth of Aglianico grapevine cultivar, with a standard clone population on 1103 Paulsen rootstocks, was studied on two different types of soil: Calcisols and Cambisols occurring along a slope of 90 m length with 11% gradient. The agro-hydrological model SWAP was calibrated and applied to estimate soil-plant water status during three consecutive seasons (2011–2013). Crop water stress index (CWSI), as estimated by the model, was related to leaf water potential, sugar content of grape bunches and wine quality (e.g. content of tannins). For both soils, the correlations between quality measurements and CWSI were high (e.g. − 0.97** with sugar; 0.895* with anthocyanins in the grape skins). The model was also applied to explore effects of future climate conditions (2021–2051) obtained from statistical downscaling of Global Circulation Models (AOGCM) and to estimate the effect of the climate on CWSI and hence on grape quality. Effects of climate change on grape quality indicate: (i) a resilient behavior of Calcisol to produce high quality wine, (ii) a good potentiality for improving the quality wine in Cambisol. The present study represents an example of multidisciplinary approach in which soil scientists, hydro-pedologists, crop modellers, plant physiologists and oenologists have integrated their knowledge and skills in order to deal with the complex interactions among different components of an agricultural system. Highlights: Evaluation of climate change impacts on Aglianico grape quality in different soils. The results confirm the potentiality of simulation modelling application in viticulture. The simulated crop water stress index, was highly correlated to grape quality. Resilience behavior of "Terroir concept" under climate change